PEMODELAN INFRASTRUKTUR MENGGUNAKAN FRAMEWORK OIAM (STUDI KASUS PS. AS PUTRA) - Aji Permana (FKOM UNIKU, 2015)
PS. AS PUTRA is a company engaged in chickens and feed distributors. PS. AS PUTRA a company which has been implementing ICT in business processes but existing infrastructure is still not good. Therefore, it needs a special model of defining the infrastructure, so that the existing infrastructure can be targeted in order to obtain a description of the infrastructure required for the development of infrastructure and enterprise systems PS. AS PUTRA.Â Open Infrastructure Architecture Model is a framework that is able to bring the company achieve the desired objectives with concrete measures to ensure the optimal use of architecture. OIAm able to define the